Weight and Abdominal Pressure-Induced Shunt Trouble in Patients With Shunted Normal Pressure Hydrocephalus: A Comprehensive Study on Pressure Environment of Shunt System - Kamo, Masatsugu; Kajimoto, Yoshinaga; Ohmura, Tomohisa; Kameda, Masahiro; Tucker, Adam; Miyake, Hiroji; Wanibuchi, Masahiko (Frontiers in Neurology, 2022)
Objectives We identified a new type of shunt malfunction (SM) in patients with normal pressure hydrocephalus (NPH). It is induced by weight change and can be treated with valve readjustment. There were two types of SM as follows: Underdrainage induced by the weight gain and overdrainage induced by the weight loss. This study aims to elucidate this mechanism by assessing the shunt pressure environment. Methods The total pressure environment of the shunt system was prospectively studied in patients with shunted NPH at Osaka Medical College Hospital from 1999 to 2005. We measured the pressure environment during the initial pressure setting of the valve by the intracranial pressure (ICP) guide, after setting the valve, and when SM was suspected. We evaluated ICP, intra-abdominal pressure (IAP), and hydrostatic and perfusion pressures of the shunt system in the sitting and supine positions. The target ICP for valve setting was empirically set at the range from −8 to −13 mm Hg in the sitting position, referring to the external auditory meatus. During the study period, we identified five cases of SM induced by weight change and assessed the changes in the pressure environment across pre-SM, SM, and post-SM. Results In four cases of underdrainage, gait disturbance worsened with an average weight gain of 6.8 ± 1.2 kg. With weight gain, IAP and ICP increased by 8.8 ± 1.6 and 4.8 ± 1.0 mm Hg, respectively. Consequently, ICP increased to −6.5 ± 1.9 mm Hg. One overdrainage patient developed an asymptomatic chronic subdural hematoma (CSDH) with a weight loss of 10 kg. With the weight loss, both IAP and ICP decreased by 5 mm Hg, and concomitantly, ICP decreased to −18 mm Hg. In all patients, the valve readjustment restored their ICP to the target pressure. After the valve readjustment, the gait disturbance improved immediately, and the CSDH disappeared after 1 month. Conclusion In patients with shunts, the weight change was linked to ICP via IAP. Due to the weight change, the underdrainage occurred when ICP was above the target pressure, and the overdrainage occurred when ICP was below it. We named this SM as the weight and abdominal pressure-induced shunt trouble. The patients with SM along with weight changes should be the first to be tried for the valve readjustment.